The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/brain/awx327
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter deficits from frontotemporal lobar degeneration

Abstract: Murley and Rowe review the neurochemical changes arising from frontotemporal lobar degeneration, including the syndromes frontotemporal dementia, progressive supranuclear palsy and corticobasal degeneration. The evidence base from in vivo and post-mortem human studies, and preclinical models, suggests new strategies to facilitate the development of symptomatic pharmacological treatments, in stratified populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
126
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(153 citation statements)
references
References 251 publications
18
126
3
Order By: Relevance
“…We have recently reported a high frequency of autoantibodies recognizing the GluA3 subunit of AMPARs in patients with FTD , corroborating the role of glutamate neurotransmission in this disorder (Murley and Rowe, 2018). Furthermore, in both rat hippocampal neuronal primary cultures and in human neurons derived from iPSCs, we demonstrated that anti-GluA3 antibodies were detrimental for neurons and for AMPA function .…”
supporting
confidence: 75%
“…We have recently reported a high frequency of autoantibodies recognizing the GluA3 subunit of AMPARs in patients with FTD , corroborating the role of glutamate neurotransmission in this disorder (Murley and Rowe, 2018). Furthermore, in both rat hippocampal neuronal primary cultures and in human neurons derived from iPSCs, we demonstrated that anti-GluA3 antibodies were detrimental for neurons and for AMPA function .…”
supporting
confidence: 75%
“…These changes seem to reflect the pharmacological abnormalities which are now clearly associated with FTLD, particularly in serotonin, dopamine, GABA and glutamate, possibly reflecting the underlying pathological process [30,31]. In particular, we observed a significant impairment in SICI and LICI, which indirectly and partially depend on GABA A and GABA B ergic transmission, respectively, and an impairment in ICF, which partly relies on glutamatergic circuits, in all FTD phenotypes.…”
Section: Discussionsupporting
confidence: 52%
“…As SICI and LICI are considered to reflect short‐lasting postsynaptic inhibition mediated through the GABA A and GABA B receptors at the level of local interneurons, and ICF is thought to represent a net facilitation most likely mediated by glutamatergic N‐methyl‐D‐aspartate receptors, the impairment observed in FTD suggests a deficit of GABAergic and glutamatergic interneurons . On the other hand, Aβ peptides have been shown to impair acetylcholine synthesis and release, and to induce cholinergic cell toxicity, which could reflect the impairment of SAI observed in AD .…”
Section: Discussionmentioning
confidence: 99%
“…As SICI and LICI are considered to reflect short-lasting postsynaptic inhibition mediated through the GABA A and GABA B receptors at the level of local interneurons, 36,37 and ICF is thought to represent a net facilitation most likely mediated by glutamatergic N-methyl-D-aspartate receptors, 11,37 the impairment observed in FTD suggests a deficit of GABAergic and glutamatergic interneurons. [49][50][51] On the other hand, Aβ peptides have been shown to impair acetylcholine synthesis and release, and to induce cholinergic cell toxicity, 52 which could reflect the impairment of SAI observed in AD. [12][13][14][15][16][17][18][19][20][21] In the same view, the well-recognized cholinergic deficit and the documented impairment of GABAergic and glutamatergic neurotransmission in DLB might explain the impairment of both SAI and SICI-ICF in these patients.…”
Section: Discussionmentioning
confidence: 99%